Alzheimer’s Disease : Silent Danger in Elderly - Choombuathong, Anchalee (Journal of Health Science of Thailand, 2017)
Alzheimer’s disease is a common form of dementia among elderly characterized by a slow decline in memory, language, skills, personality and cognition. The cause of Alzheimerี s disease remains unknown, but there appears to be a relationship among genetic predisposition, the abnormal processing of neuronal cell, aggregation of amyloid plaque and decrease of neurotransmitter such as, acetylcholine. Symptoms of Alzheimer’s disease include memory loss, especially recent events, loss of the ability to think logically and unable to do simple tasks. Although there is no cure for Alzheimer’s disease, medications can control the systems and the progression of the disease. Drug therapies for Alzheimer’s disease associated systems are often effective such as tacrine (CognexÒ) and donepezil (AriceptÒ) which increase circulating levels of acetylcholine. Non steroidal anti-inflammatory drug-NSAID is used for treatment of anti-inflammation response amyloid plaque aggregation. Vitamin E in a high dose also appear to delay the progression of disease, presumably by controlling the effects of free radical damage. Also estrogen replacement therapy appears to be an effective treatment in menopausal woman and Alzheimer’s disease. Management of clients with Alzheimer’s disease is a challenge. The client’s family must provide mental care and memory stimulation, recognition and maintain daily living normalcy. In addition, The warning signs of Alzheimer’s disease should be rapidly recognized as the disease mimics other signs of old age. This information regarding the type of symptoms related to disease can be helpful to family in decision on whether more evaluation and the early treatment are needed.